2014
DOI: 10.1002/eat.22340
|View full text |Cite
|
Sign up to set email alerts
|

Central coherence in adolescents with bulimia nervosa spectrum eating disorders

Abstract: Poorer accuracy scores reflect a fragmented and piecemeal strategy that interferes with visual-spatial integration in BN spectrum disorders. This cognitive inefficiency likely contributes to broad difficulties in executive functioning in this population especially in the context of worsening bulimic symptoms. The findings of this study support the hypothesis that poor global integration may constitute a cognitive endophenotype for BN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 24 publications
3
26
0
2
Order By: Relevance
“…Evidence from cognitive tasks support deficits in executive functions (EFs), or a set of cognitive processes that support higher order cognitive abilities and goal attainment [29], in both children with obesity [30] and disordered eating [31]. Children with comorbid obesity and dysfunctional eating may have a cognitive profile that is distinct and more deficient then youth with obesity alone [32, 33].…”
Section: Correlates Of Dysfunctional Eating In Children With Obesitymentioning
confidence: 99%
“…Evidence from cognitive tasks support deficits in executive functions (EFs), or a set of cognitive processes that support higher order cognitive abilities and goal attainment [29], in both children with obesity [30] and disordered eating [31]. Children with comorbid obesity and dysfunctional eating may have a cognitive profile that is distinct and more deficient then youth with obesity alone [32, 33].…”
Section: Correlates Of Dysfunctional Eating In Children With Obesitymentioning
confidence: 99%
“…Additionally, poor inhibitory control (i.e., the ability to inhibit a prepotent response) has been observed in EDs characterized by binge eating (Fischer, Smith, & Anderson, 2003; Rosval et al, 2006; Wu et al, 2013). Converging evidence that deficits in EF are present in adolescents who have a short duration of ED illness (Darcy et al, 2012, 2014; Fitzpatrick et al, 2012), and that deficits remain following symptom remission (Holliday et al, 2005; Lopez et al, 2009; Roberts et al, 2007, 2010), suggest that these traits could be causal rather than consequential (though there is likely to be some degree of bi-directionality) (Kanakam & Treasure, 2013). …”
Section: Neurocognitive Deficits In Eating Disordersmentioning
confidence: 99%
“…Although there is less research, studies with individuals with Bulimia Nervosa (BN) have also demonstrated poor global processing in comparison to healthy controls (HCs); suggesting that this processing style is a trans-diagnostic characteristic amongst EDs [9,12,13]. …”
Section: Introductionmentioning
confidence: 99%